Identification of Novel Hemangioblast Genes in the Early Chick Embryo - Serrado Marques, José (2018)
During early vertebrate embryogenesis, both hematopoietic and endothelial lineages derive from a common progenitor known as the hemangioblast. Hemangioblasts derive from mesodermal cells that migrate from the posterior primitive streak into the extraembryonic yolk sac. In addition to primitive hematopoietic cells, recent evidence revealed that yolk sac hemangioblasts also give rise to tissue-resident macrophages and to definitive hematopoietic stem/progenitor cells. In our previous work, we used a novel hemangioblast-specific reporter to isolate the population of chick yolk sac hemangioblasts and characterize its gene expression profile using microarrays. Here we report the microarray profile analysis and the identification of upregulated genes not yet described in hemangioblasts. These include the solute carrier transportersSLC15A1andSCL32A1, the cytoskeletal proteinRhoGap6, the serine proteaseCTSG, the transmembrane receptorMRC1, the transcription factorsLHX8,CITED4andPITX1, and the previously uncharacterized geneDIA1R. Expression analysis by in situ hybridization showed that chickDIA1Ris expressed not only in yolk sac hemangioblasts but also in particular intraembryonic populations of hemogenic endothelial cells, suggesting a potential role in the hemangioblast-derived hemogenic lineage. Future research into the function of these newly identified genes may reveal novel important regulators of hemangioblast development.